2011
DOI: 10.1051/kmae/2011013
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of bacteria and intensity of microbiological processes in two stratified gypsum Karst Lakes in Lithuania

Abstract: Key-words:bacteria, microbial processes, karst lakes Physical-chemical parameters and the vertical distribution of bacteria and organic matter production-destruction processes were studied during midsummer stratification in two karst lakes (Kirkilai and Ramunelis) located in northern Lithuania. The lakes were characterized by high sulfate concentrations (369−1248 mg·L −1 ). The O 2 /H 2 S intersection zone formed at 2−3 m depth. In Lake Kirkilai, the highest bacterial densities (up to 8.7 × 10 6 cell·mL −1 ) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These lakes are mainly small, but relatively deep and often stratified. The hydrochemical facies of these water bodies are typical complexes of predominating solutes, pointing toward definite climatic and, accordingly, geochemical (weathering), soil, and hydrogeological and hydrobiological conditions, under which lake waters acquire their concentrations and compositions [3,4]. Gypsum karst lakes are characterized as sulphate lakes, as they are rich in gypsum or calcium sulphate, and they have elevated conductivity values [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These lakes are mainly small, but relatively deep and often stratified. The hydrochemical facies of these water bodies are typical complexes of predominating solutes, pointing toward definite climatic and, accordingly, geochemical (weathering), soil, and hydrogeological and hydrobiological conditions, under which lake waters acquire their concentrations and compositions [3,4]. Gypsum karst lakes are characterized as sulphate lakes, as they are rich in gypsum or calcium sulphate, and they have elevated conductivity values [5].…”
Section: Introductionmentioning
confidence: 99%
“…These lakes are brackish (dissolve salts up to 2.0 g/L) and often cold water. Some have powerful springs of underground water pressure, specific water balances, amplified water exchanges, high transparency, and azure (ultramarine) water colors [4,6]. On the global scale, surface outcrops of gypsiferous strata appear quite limited [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…depth 6-7 m), nutrient-and organic matter-rich water body with high concentrations of Ca 2+ and SO 4 2− ions [27]. During summer stratification, the lake exhibits a pronounced chemocline at approximately 2 m deep, which is noticeable due to the depletion of oxygen, changes in water conductivity, and the presence of hydrogen sulfide (H 2 S) [28][29][30]. These conditions are also accompanied by a significant shift in water temperature and density.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions are also accompanied by a significant shift in water temperature and density. Previous studies based on pigment analysis and partial 16S rRNA gene sequences obtained from the enrichment cultures revealed that members of genera Chlorobium (green sulfur-oxidizing bacteria; GSB) and Desulfovibrio (sulfate-reducing bacterium; SRB) are prevalent in the euxinic water layers of Lake Kirkilai [28][29][30]. At present, however, the relative abundance and distribution of these species, and any associations with other members of the lake bacterial or viral communities, are unknown.…”
Section: Introductionmentioning
confidence: 99%